Evaluation of retinectomy in the treatment of severe proliferative vitreoretinopathy. Issue 1 (December 2015) - Mendes, Thaís; Gomes, André; Rocha, Bruno; Passos Junior, Hélcio; Abujamra, Suel
Abstract Background To evaluate the postoperative results and efficacy of retinectomy in the treatment of severe proliferative vitreoretinopathy (PVR). Methods The study involved 38 individuals with rhegmatogenous retinal detachment initially diagnosed with PVR grade C3 who had undergonepars plana vitrectomy combined with scleral buckle and silicone oil as a tamponade. A standard three-portpars plana vitrectomy was performed, and the extension of performing a retinectomy was decided during the procedure. The patients were followed for a minimum of 6 months after the last surgical procedure. Reoperation, postoperative hypotony and final reattachment rates were evaluated. Statistical analysis was performed with an Exact Fisher's test. Results The mean preoperative visual acuity was >1.3 logMAR. The postoperative visual acuity improved and ranged from 1.3 to 0.7 logMAR (p < 0.63). The preoperative intraocular pressure was 10.2 mmHg and postoperatively was 11.6 mmHg. Postoperative hypotony was observed in 15.8 % of the cases. The reoperation rate after the first procedure was 63.2 %. A total of 44.7 % of the patients needed a retinectomy greater than 270° for a final anatomical success. The final retinal reattachment rate was 94.7 %. Conclusions Retinectomy can be an effective surgical procedure in the treatment of severe PVR, and it may increase the final reattachment rate.